2020
DOI: 10.5267/j.msl.2019.8.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of contextual factors, government, corporate social responsibility and competency on business development

Abstract: This study aims to analyze the influence of contextual factors, government role, implementation of corporate social responsibility, and competency on competitiveness of wood craft Small Medium Industries (SMI) in Bali Province, Indonesia. The renewal of this research is to include the implementation of CSR in order to improve business competencies and competitiveness of SMIs. A sample of 152 respondents from the wood crafts SMIs in Bali Province. The research approach used is quantitative (positivist) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Therefore, the results of this study show a significant positive effect between competitiveness and the performance of fishing companies. The identification of these influences is consistent with the research findings (Anwar et al, 2018;Bernal-Conesa et al, 2017;Cantele & Cassia, 2020;Famiyeh, 2017;Kiyabo & Isaga, 2019;Potjanajaruwit, 2018;Priyanka et al, 2017;Rua et al, 2018;Saeidi et al, 2015;Sigalas & Papadakis, 2018;Yuniarta et al, 2020). However, the results of this study are contradictory with Astuti et al (2018); Bagur-Femenías et al (2015) who found that competitiveness has no significant effect on firm performance.…”
Section: Discussion and Research Implicationssupporting
confidence: 88%
See 2 more Smart Citations
“…Therefore, the results of this study show a significant positive effect between competitiveness and the performance of fishing companies. The identification of these influences is consistent with the research findings (Anwar et al, 2018;Bernal-Conesa et al, 2017;Cantele & Cassia, 2020;Famiyeh, 2017;Kiyabo & Isaga, 2019;Potjanajaruwit, 2018;Priyanka et al, 2017;Rua et al, 2018;Saeidi et al, 2015;Sigalas & Papadakis, 2018;Yuniarta et al, 2020). However, the results of this study are contradictory with Astuti et al (2018); Bagur-Femenías et al (2015) who found that competitiveness has no significant effect on firm performance.…”
Section: Discussion and Research Implicationssupporting
confidence: 88%
“…Competitiveness is believed to be a driving force for growth and a tool for assessing the success of companies in various industrial sectors because competitiveness has been significantly proven to be a determining factor for economic growth and development. Furthermore, the current research seeks to explain that company performance cannot be increased directly from environmental uncertainty (Cantele & Cassia, 2020;Junquera & Barba-Sánchez, 2018;Priyanka et al, 2017;Yuniarta et al, 2020), however through the role of competitiveness. From several studies, for example Bagur-Femenías et al (2015); Harash (2015) found the effect of environmental uncertainty on firm performance is significantly mediated by competitiveness.…”
Section: The Role Of Mediation Of Competitivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, competence. Previous research has shown that competence influences employee performance [49][50] [51]. This is as seen in studies conducted by Although many studies have supported the assumption that if employees already have a sense of satisfaction at work it will create productive human resources that can improve the performance of these employees, theoretically there is still the very little relationship between competence and job satisfaction with employee performance.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%